A formação continuada de docentes de ensino religioso para o ensino fundamental (anos iniciais) a partir da coleção de livros didáticos Nautas - Xavier, Magno de Carvalho (2023)
The purpose of this research is to study the theme of the ongoing teacher´s formation for Religious Education. It intends to analyze the Cycle of the ongoing formation carried out by the Brazil Salesian Network of Schools, between the years of 2020 and 2022, based on a collection of textbooks which is placed as consistent with the BNCC. For this reason, through bibliographical research, we dialogued with authors who deal with the theme of Ongoing Teacher´s Formation, among them: Paulo Freire, Maurice Tardif and Francisco Imbernón and with specialists who made their research with the theme of Religious Education, according to the BNCC, among them are: Sérgio Junqueira and Elisa Rodrigues. After presenting some characteristics of the Salesian Network, through documentary research, we analyzed the collection of textbooks for elementary school - early years, Nautas. The Salesian Network was the place where the ongoing formation cycle that will be analyzed in this paper took place and the Nautas teaching material was the main reference used for this formation. Therefore, by presenting the experience conducted in the Salesian Confessional Network, we hope to contribute to the reflection on the importance of ongoing teacher´s formation from the perspective of the BNCC. As we shall see, such perspective aims at a society where different people do not annihilate each other, but complement each other, fostering dialogue and the culture of peace.